Compliance of banks to the Anti-Money Laundering legislation: The case of the European Union - Thonon, Mathilde (2006)
Money Laundering is the process by which the criminal will be able to enjoy the proceeds of his criminal activities. It involves the placement of dirty money into the legitimate banking system. That is the reason why bankers are in the first line in the fight against money laundering. They should be thus responsible in the poor results in the application of the Anti-Money Laundering legislation. This work will identify the different laws that regulate the bankers in the prevention of money laundering, with a focus on the European Union law. The dissertation will revolve around the analysis of three case studies: the Anti-Money Laundering (AML) legislation in the United-Kingdom, France and Belgium. Evidence will be supported by interviews of actors in the AML fight. This dissertation analyses the degree of compliance of the banks and the reasons why, although the bankers are motivated to comply with the legislation, worldwide criminals are still laundering trillions of dollars per year. An analysis of the case studies and of the material available can highlight several loopholes in the behavior of the bank that allow dirty money to enter the legal banking system. Those loopholes will be discussed, and a rival theory will be formed: The money launderers tend to rely much less on the banks than they used to, they use other regulated professions to enter the banking system. This paper will finally draw a broad picture of the different problems whose combination causes the criminal activities to be still a thriving business.